Panama : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2012)
The 2011 Article IV Consultation reports that Panama's economy has rebounded strongly from the 2009 slowdown, and is one of the fastest-growing in the region. Rapid growth and prudent fiscal policy have lowered public debt to less than 40 percent of GDP, and rating agencies have placed Panama's sovereign debt one notch above investment grade. The neutral fiscal stance envisaged for 2012-13 is broadly appropriate, though a tighter stance would have been preferable to rebuild buffers and contain inflation.